Underrepresentation of Sacred Text Studies in Students’ Theses: Evidence from a Religious Studies Program in Indonesia - Khairullah Zikri; Saniatul Hidayah; Raya Moniqa Atilla; Roma Wijaya (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the position and representation of sacred text studies in undergraduate and graduate theses within the Religious Studies Program at Sunan Kalijaga State Islamic University, Indonesia, and explores the factors associated with their relatively limited presence. The study is important in light of the growing prominence of empirical and interdisciplinary approaches in Religious Studies, which may influence students’ research orientations and the balance between textual and contextual inquiry. This research employs a qualitative approach with descriptive survey elements. Data were collected through document analysis of 100 thesis titles produced between 2020 and 2024, a checklist-based questionnaire administered to 30 respondents, and in-depth interviews with five lecturers and three students. The data were analyzed interpretatively to identify thematic patterns, associated factors, and students’ perceived academic support needs. The findings show that sacred text studies appear in only seven titles, or 7% of the total theses analyzed, while most student research is oriented toward sociological, cultural, interreligious, and other contextual approaches. Their limited representation is associated with structural constraints, methodological challenges, and students’ preferences for topics perceived as more practical and manageable. The study implies that strengthening textual methodology training, improving access to primary sources, and enhancing expert supervision may help create a more balanced academic environment. The originality of this study lies in its micro-academic focus on student thesis practices, offering an empirical account of how disciplinary orientations are shaped within a specific Religious Studies program.